2022
DOI: 10.1186/s12939-022-01741-1
|View full text |Cite
|
Sign up to set email alerts
|

Equity and efficiency of public hospitals’ health resource allocation in Guangdong Province, China

Abstract: Background To better meet people’s growing demand for medical and health services, 21 cities in Guangdong Province were involved in the reform of public hospitals in 2017. This paper evaluates the equity and efficiency of public hospitals’ health resource allocation in Guangdong Province and explores ways to change the current situation. Methods Data were collected from the Guangdong Health Statistical Yearbook 2016–2020 and Guangdong Statistical Y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 44 publications
2
27
0
1
Order By: Relevance
“…The results of e ciency and productivity show that the allocation e ciency of MCH resources in Henan Province is not high. The average TE for MCH institutions for 2016-2020 was 0.827, lower than studies in South Korea (0.886), Palestine (0.853) 37 , and other Chinese Provinces, including Guangdong (0.891) 9 , Jiangsu (0.920) 8 , Taiwan (0.973) 38 , and Wuhan (0.899) 39 , but still higher than Oman (0.692), Serbia (0.782) 40 , Turkey (0.724) 41 , Saudi Arabia (0.760) 42 , and Jordan (0.547). In 2016-2020, no more than half of the cities in Henan Province are DEA e cient each year, indicating that health resources in most cities are not being fully utilized.…”
Section: Discussionmentioning
confidence: 56%
“…The results of e ciency and productivity show that the allocation e ciency of MCH resources in Henan Province is not high. The average TE for MCH institutions for 2016-2020 was 0.827, lower than studies in South Korea (0.886), Palestine (0.853) 37 , and other Chinese Provinces, including Guangdong (0.891) 9 , Jiangsu (0.920) 8 , Taiwan (0.973) 38 , and Wuhan (0.899) 39 , but still higher than Oman (0.692), Serbia (0.782) 40 , Turkey (0.724) 41 , Saudi Arabia (0.760) 42 , and Jordan (0.547). In 2016-2020, no more than half of the cities in Henan Province are DEA e cient each year, indicating that health resources in most cities are not being fully utilized.…”
Section: Discussionmentioning
confidence: 56%
“…Compared with the West, the Central has not bene ted from preferential regional policies, making it the most vulnerable region. Meanwhile, the western region has a limited level of technology, but relatively appropriate and fully utilized inputs [56][57].…”
Section: Discussionmentioning
confidence: 99%
“…A systematic literature review showed that among approximately 218 indicators used in hospital performance evaluations, the average LoS and BOR are the most frequently used [12]. Currently, there are several indicators available that can objectively re ect the allocation and utilization of bed resources, including average LoS, bed turnover times, and occupancy rate [13,14]. In this study, bed-related and economic indicators, including the BOR, bed turnover time, LoS, waiting time, and total patient hospitalization cost, were used for statistical analysis.…”
Section: Indicator Selectionmentioning
confidence: 99%